An Improved DP Compression Algorithm of Wireless Sensor Network - Deyu Zhang; Zheng Li; Yanhui Lv; Zhiwei Qu (IMCCC 2016 : proceedings, 2016 sixth International Conference on Instrumentation & Measurement, Computer, Communication and Control : Harbin, Heilongjiang, China, 21-23 July 2016, 2016)
Because there are the following problems in the wireless sensor network: the collected data redundancy degree is higher, the node energy is limited, and the node storage is limited and so on, this paper puts forward an improved DP data compression algorithm, that is, the collected data is transmitted after they are firstly compressed. Adopt the method of automatically setting the compression threshold value to reduce the influence of personal factor on the compression process, use the best curve fitting algorithm to fit the curve to reduce the random error and increase the compression precision, use the step length and stack technologies to decrease the frequency of scanning of data point and reduce the energy consumption of node. The simulation result indicates that the improved DP compression algorithm is batter than the DP compression algorithm in the aspects of compression precision and the energy consumption of node, and therefore, it is more suitable for the wireless sensor network whose energy and storage are limited.